Optimization of construction project time for type 85 boarding house using a simple path method - Away, Johan Lucas; Nurhasanah, Siti; Hatta O, Darul; Pratama D, Rio; Ramandha P, Daffa (Institute of Computer Science (IOCS), 2025)
The growth of the construction sector in Indonesia has driven high demand for rental housing, such as boarding houses, especially in major cities like Samarinda. However, delays in construction projects remain a common issue that can affect cost efficiency and investment potential. The purpose of this study is to evaluate the effectiveness of the simple Critical Path Method (CPM) in optimizing the construction time of a Type 85 boarding house project in Samarinda City. CPM is applied through activity mapping, duration determination, and the creation of a work network diagram. Data were obtained through field observations, project documentation studies, and interviews with contractors. The analysis results show that the project's critical path consists of a series of activities: A – B – C – D – H – F – G – I – J – K – L. By using CPM method, The project timeline can be shortened from 333 days to 283 days, leading to a 15% reduction in duration.These findings indicate that even in its simplified form, the application of CPM can improve time efficiency and help small subcontractors manage projects in a more organized and timely manner